"Too cumbersome": questionnaires in cases of criminal communities - A. E. Bosov; T. N. Bashirov (Russian Journal of Economics and Law)
Objective: basing on comprehensive legal and linguistic techniques, to analyze the questionnaires in cases of criminal communities, for compliance to part 8 of Article 339 of the Russian Criminal-Procedural Code, referring to comprehensibility of the questions for the jurors. Methods: the study was conducted using the combined method, which included the formal-legal and legal-technical methods, traditional legal science, and the theory of speech acts and special linguistic methodology "logical analysis of the language". Results: The analysis of the questionnaires and judicial acts of the Supreme Court showed that, despite frequent complaints, arguments about the incomprehensibility and bulkiness of the analyzed questionnaires, they are in most cases recognized as unreasonable. This is due to the extensive list of the questionnaires and complexity of the issues, due to the volume of the sustained charges and is not in itself an evidence of the violation of part 8 of Article339 of the Criminal-Procedural Code. Scientific novelty: A questionnaire, being a specific legal document, oriented on a citizen (juror) and compiled taking into account the division of the professional judge and jury’s competences, is of the common language nature. The study showed that legal assessment is most effective with professional (not amateur) combination of research methods from different scientific fields - law and linguistics. Practical value: Answering the arguments of the complaints about the incomprehensibility and volume of cases studied by the jury, judges of the Supreme Court of the Russian Federation estimate of questionnaires from the perspective of their own linguistic competence, i.e., the amateur, from the point of view of linguists, level and almost always intuitively. The authors' recommendations can help the presiding judge, who poses the questions to the jury, and will allow superior judges to give a more professional and well-reasoned legal and linguistic evaluation of the analyzed questionnaires. The convenience of our findings lies in the fact that they are succinctly formulated in the form of additions to the decree of the Russian Federation Supreme Court Plenum no. 23 of November 22, 2005 "On application by courts of the norms of the Criminal Procedural Code of the Russian Federation, regulatory legal proceedings with the participation of jurors" (about the interpretation and application of part 8 of Article 339 of the Criminal Procedural Code of the Russian Federation).